EFEKTIFITAS WORD OF MOUTH (WOM) DALAM KOMUNIKASI PEMASARAN ROTTE BAKERY PEKANBARU - Hendra, Muhammad David; Muhammad Arif; M. Hadi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
This study aims to determine how the Effectiveness of Word Of Mouth (WOM) in Marketing Communications Rotte Bakery Pekanbaru. The population in this study were Rotte Bakery Consumers, Tampan Pekanbaru District, namely male and female. The total number of people in the Tampan District who became the population in this study was 307,947 people. The number of samples to be taken for this research is 100 respondents, this sample is determined according to the Slovin formula. The data analysis techniques used in this research are validity test, reliability test, normality test, simple linear regression test and hypothesis testing using t test using SPSS 23 software. The value of R Square or the Coefficient of Determination (KD) shows the regression model formed by the interaction of the independent variable and the dependent variable. The KD value obtained is 0.521. So it can be interpreted that the independent variable X has a contribution effect of 52.1% on the Y variable. On the influence of some marketing communications other than Word Of Mouth (WOM), it is possible that there are communication strategies other than Word Of Mouth (WOM) communication, which is 47.9%. That the t-test calculation is t-count 10,333 > t- table 1,984 at a significance level of 5% (0.05) which means that Ha is accepted, namely Word Of Mouth Communication (WOM) in Effective Rotte Bakery Marketing Communication.